Molecular epidemiology and genetic evolution of PRRSV ORF5 in Sichuan, Southwest China - Yu, Jifeng; Kang, Runmin; Qing, Yi; Xu, Qingsong; Xie, Jing; Cao, Ye; Ye, Yonggang; Xiao, Lu; Xie, Lei; Xiang, Xiaoxue; Zhou, Long; Yu, Changqing; et al. (Frontiers in Microbiology, 2026)
BackgroundPorcine reproductive and respiratory syndrome virus (PRRSV) is a major economic threat to the global swine industry. In China, PRRSV undergoes continuous evolution through frequent mutation and recombination, driving the emergence of diverse genotypes. This is of particular concern in Sichuan Province, a major swine-producing region in Southwest China, where recurrent PRRSV outbreaks have led to substantial economic losses.ObjectivesThis study was designed to investigate the epidemiological patterns and genetic evolution of PRRSV in Sichuan Province by analyzing the ORF5 gene. We collected samples from five major swine-producing cities (Chengdu, Mianyang, Meishan, Ya’an, and Yibin) throughout 2024. Our objectives were to determine the lineage distribution, assess sequence diversity, and identify key amino acid variations among the circulating strains. The findings aim to provide a molecular basis for informing and refining regional PRRSV control strategies.MethodsA total of 658 suspected PRRSV samples were collected from large-scale pig farms across the five cities. Clinical samples mainly included serum and tissue samples (such as lung and lymph node tissues) obtained from pigs showing PRRS-like symptoms during routine diagnostic procedures. The ORF5 gene was amplified by RT-PCR, sequenced, and analyzed for nucleotide and amino acid homology. Phylogenetic trees were constructed using MEGA 11 and EvolView to determine lineage classification. GP5 amino acid sequences were further examined to identify key mutations within signal peptides, transmembrane regions, and neutralizing epitopes.ResultsAmong the 658 samples, 185 (28.16%) were PRRSV-positive. Phylogenetic analysis of 53 representative ORF5 sequences revealed that all isolates belonged to PRRSV-2: 20 samples were NADC30-like (37.73%) strains, 1 samples were NADC34-like (1.89%) strains, 3 samples were QYYZ-like (5.66%) strains, 17 samples were VR2332-like (32.08%) strains, and 12 samples were JXA1-like (22.64%) strains. Multiple amino acid substitutions and deletions were detected in the GP5 protein, particularly in signal peptides, neutralizing epitopes, and transmembrane domains, indicating extensive genetic diversity.ConclusionOur findings confirm that NADC30-like strains constitute the predominant lineage circulating in Sichuan Province, with co-circulation of JXA1-like and strains with potential recombination signatures inferred from phylogenetic clustering. The prevalence of frequent mutations within GP5 antigenic regions underscores the substantial genetic diversity of PRRSV. These results emphasize the critical need for sustained molecular surveillance and the development of updated vaccines to effectively manage PRRS outbreaks in the region.